MARKET EQUILIBRIUM MODEL WITH DISCRETE DELAY DIFFERENTIAL EQUATION - Zidan Putra Irawan, Naufal
The price of a commodity in a market is closely related to demand and supply. The responses of market participants are not instantaneous, so it is necessary to consider the delay factor, especially in demand and supply. This study focuses on modeling market prices using discrete delay differential equations by modifying the model developed by Katsumasa Kobayashi and applying it to the commodity of rice. The modified model is applied in two ways: first, by creating a model with information on rice commodities in 2023 and then predicting prices in the same year, and second, by creating a model with information on rice commodities in 2022 and then predicting prices in 2023. The model’s solution is determined using the step method and integration factor with various delays and weights. The results show that the model with a delay variation of 0.1 and a weight of 0.1 provides the best predictions among other variations, although the accuracy is limited to the fourth or fifth step. The first model relatively shows a smaller error compared to the second model.